An Insight In to Functionally Generated Pathway: A Review Article - Navyadeepthi, M.; Srikanth, L.; Purnapriya, B.; Mounica, Y.; Soni, Sudeepti; Agrawal, Pooja (International Journal Of Drug Research And Dental Science, 2021)
The functionally generated path technique is a different method to achieve occlusal harmony in the oral cavity. Other than using an articulator to simulate the movement of the mandible, this technique utilizes a tracing. This is made directly in the mouth to capture the pathways travelled by the opposing cusps during mandibular function. This article discusses the functionally generated path technique in detail.